Ekman Soya Bean Company / Amalia Abu Bakar... [et al.] - Abu Bakar, Amalia; Ahmad, Nabihah; Abdul Aziz, Norliza; Samsu, Rokiah; Abu Bakar, Norasmah (2001)
Ekman Soya Bean Company is involved in the Manufacturing Soya beans such as ‘tauhu’, ‘fucuk’ and also beverages. There are 3 type of flavour for their beverage such as chocolate, strawberry and pandan. It was a partnership business. 80’s people are firstly aware of the product based on the Soya beans. As time passed by the demand of the soya beans product has increased in a progressive condition. The location of this business at Arau, Perlis.